Macrofungal conservation in Canada and target species for assessment: a starting point - Anna Bazzicalupo; Susana C. Gonçalves; Rémi Hébert; Sigrid Jakob; Alfredo Justo; Gavin Kernaghan; Renée Lebeuf; Bruce Malloch; R. Greg Thorn; Allison K. Walker (Canadian Science Publishing, 2022)
Despite the ecological importance of fungi, we still know little about their diversity in Canada. One of the largest hurdles to implementing fungal conservation initiatives is the lack of fungal distribution data. As anthropogenic impacts accelerate the speed of environmental change, it is imperative that we fill this major information gap, critical for fungal protection. To gain insight on the conservation status of Canadian macrofungi, we took advantage of the large and growing body of fungal biodiversity data from government research (Wild Species 2020), citizen science, trained independent mycologists, university, and museum biodiversity research. The majority of macrofungi are data deficient; we do not know their geographic distribution or habitat requirements, occurrence, or abundance in Canada. For mushrooms that fruit only a few days of the year and are often difficult to positively identify, there is a lot of work to overcome the uncertainty of distinguishing under-sampling from rarity. Our work stresses the importance of building a strong network of professional and amateur mycologists to develop resources, disseminate information to make educated decisions, and advance conservation actions. We found that several fungi can be prioritized; we present a short list for consideration for formal conservation assessment.